Tourism at the grassroots [ villagers and visitors in the Asia Pacific - Connell, John , 1946-; Rugendyke, Barbara (Contemporary geographies of leisure, tourism, and mobility, 2008)
This new collection focuses on both the interactions between tourists and villagers, and the impacts of tourism at the local level, considering economic, social, cultural and environmental changes.